2014
DOI: 10.1186/1471-2407-14-418
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphoma 6 protein stimulates oncogenicity of human breast cancer cells

Abstract: BackgroundB-cell lymphoma 6 (BCL6) protein, an evolutionarily conserved zinc finger transcription factor, showed to be highly expressed in various human cancers in addition to malignancies in the lymphoid system. This study investigated the role of BCL6 expression in breast cancer and its clinical significance in breast cancer patients.MethodsExpression of BCL6 protein was assessed using in situ hybridization and immunohistochemistry in 127 breast cancer patients and 50 patients with breast benign disease as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…The BCL6 protein, a zinc finger transcription factor that has been conserved throughout evolution, has demonstrated high expression levels in numerous types of human cancer, alongside lymphoid system malignancies (19). Further studies have observed potent BCL6 protein expression in various types of human cancer outside of the lymphoid system.…”
Section: Discussionmentioning
confidence: 99%
“…The BCL6 protein, a zinc finger transcription factor that has been conserved throughout evolution, has demonstrated high expression levels in numerous types of human cancer, alongside lymphoid system malignancies (19). Further studies have observed potent BCL6 protein expression in various types of human cancer outside of the lymphoid system.…”
Section: Discussionmentioning
confidence: 99%
“…Standard avidin-biotin immunohistochemical analysis of the sections was performed. The staining results were evaluated by at least three certified pathologists and the tumor cell staining was scored as follows: For FOXM1, 0 (no staining for nucleus despite of the staining result of cytoplasm or membrane), 1 (weak staining for nucleus [and cytoplasm] and area of positive staining <10%), 2 (moderate staining for nucleus [and cytoplasm] and area of positive staining among 10%–50%), and 3 (strong staining for nucleus [and cytoplasm] and area of positive staining >50%) [42, 43]; for OTUB1, 0 (no staining for cytoplasm or membrane), 1(weak positive for cytoplasm), 2(moderate positive for cytoplasm), and 3(strong positive for cytoplasm). The cases with score 0-1 were considered low and those with a score of 2-3 were considered high [42, 43].…”
Section: Methodsmentioning
confidence: 99%
“…BCL6 plays a role in promoting the invasion of breast cancer cells and the expression level of BCL6 positively associates with poor survival of breast cancer patients [5]. However, how BCL6 participates in the regulation of the development and progression of breast cancer remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…However, we did not detect any binding of BCL6 to the E-cadherin promoter (data not shown). A number of studies demonstrate that a variety of transcriptional repressors including Snail, Twist, Slug, deltaEF1/ZEB1, SIP1/ZEB2 and CtBP2 can bind to the E-cadherin promoter and inhibit the gene transcription [5][6][7][8][9][10][11][12]. We therefore screened which transcription repressor mediated the BCL6-repressed E-cadherin expression with siRNA assay.…”
Section: Bcl6 Promotes Emt Through Enhancing the Zeb1-mediated Transcmentioning
confidence: 99%
See 1 more Smart Citation